Weathering a Crisis: A Multi-Level Analysis of Resilience in Young Ventures - Anwar, Ali; Coviello, Nicole; Rouziou, Maria (Entrepreneurship Theory and Practice, 2023)
In the context of the external disruption presented by the COVID-19 pandemic, we investigate (1) how individual-level resilience and inter-functional coordination relate to organizational resilience and (2) the link between organizational resilience and firm performance. We view organizational resilience as a resource-based capability and draw on insights regarding psychological capital and relational resources to inform our hypotheses. Our hypotheses are tested with a time-lagged, multi-level study of young technology ventures. The results show that when such firms are resilient, they tend to perform significantly better in a crisis. Further, organizational resilience is positively influenced by the individual resilience of top management team members, as well as inter-functional coordination. We discuss implications for theory and practice and suggest avenues for research on resilience in entrepreneurship.